The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.jgr.2017.01.012
|View full text |Cite
|
Sign up to set email alerts
|

20 S -Protopanaxadiol, an aglycosylated ginsenoside metabolite, induces hepatic stellate cell apoptosis through liver kinase B1–AMP-activated protein kinase activation

Abstract: BackgroundPreviously, we reported that Korean Red Ginseng inhibited liver fibrosis in mice and reduced the expressions of fibrogenic genes in hepatic stellate cells (HSCs). The present study was undertaken to identify the major ginsenoside responsible for reducing the numbers of HSCs and the underlying mechanism involved.MethodsUsing LX-2 cells (a human immortalized HSC line) and primary activated HSCs, MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyl-tetrazolium bromide) assays were conducted to examine the cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…However, benzoic acid glycosides (e.g., vanillic acid 4-β-D-glucopyranoside) generally have low bioavailability due to the hydrophilicity of the conjugated glycosides. In this regard, it has been believed that the biological effects of ingested glycosylated phytochemicals result from the aglycone metabolites produced during absorption [ 37 , 38 ]. Of various phytochemicals aforementioned, not only vanillic acid, but also syringic acid and vanillin have been reported to protect the lungs from toxic stimuli [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…However, benzoic acid glycosides (e.g., vanillic acid 4-β-D-glucopyranoside) generally have low bioavailability due to the hydrophilicity of the conjugated glycosides. In this regard, it has been believed that the biological effects of ingested glycosylated phytochemicals result from the aglycone metabolites produced during absorption [ 37 , 38 ]. Of various phytochemicals aforementioned, not only vanillic acid, but also syringic acid and vanillin have been reported to protect the lungs from toxic stimuli [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…8 Research has shown that RG and its components, such as fermented RG and 20(S)-protopanaxadiol, can exert antioxidative and anti-inflammatory effects on liver tissue, contributing to the overall protection of liver function. [9][10][11] The unique phytochemical profile of RG, comprising saponins (notably ginsenosides), flavonoids, polyacetylenes, and polysaccharides, underpins its therapeutic potential. 12 Another study suggested that the hepatoprotective properties of RG are exerted through the activation of the AMPK pathway, which defends against oxidative damage and supports liver health.…”
Section: Introductionmentioning
confidence: 99%
“…Because ginsenosides possess a common four-ring hydrophobic steroid-like structure with sugar moieties attached at C-3, C-6 or C-20 position, they can be divided into four subtypes as protopanaxadiol (PPD), protopanaxatriol (PPT), oleanolic acid, and octillol [6] . Owing to the diversity of chemical structure, the naturally occurring saponins exhibit a wide range of polarity and hydrophobicity, resulting in their distinct biological activities [7] .…”
Section: Introductionmentioning
confidence: 99%